MAPPING THE DISTRIBUTION OF VOLCANIC DEBRIS AVALANCHE DEPOSITS IN THE DISTAL ZONE OF THE ANCIENT LANDSLIDE OF MT. RAUNG, AT JEMBER AREA, EAST JAVA - Hadid Rahman Ulfa, Abd.
The Southeast region of Jember Regency in East Java, is known as the "city of a thousand hummocks". These volcanic hummocks are primarily composed of silt material (sand as matrix and stone as fragments) which are volcanic products. This study aims to identify the distribution of volcanic hummocks in the distal zone of the ancient landslide of Mt. Raung. The techniques employed include using Planetscope imagery with a resolution of 3.7 meters, aerial photograph at a resolution of 0.13 meters, and DEMNAS with a resolution of 8.25 meters. Vegetation Indices and Object-Based Image Analysis (OBIA) methods were used in this study to identify volcanic hummocks based on land cover classification. The land cover classification accuracy demonstrated that the OBIA method was highly accurate, with a Kappa value of 79.26%. Meanwhile, the NDVI, SAVI, and MSAVI Vegetation Indices had Kappa values that indicate moderate accuracy. The correlation between volcanic hummocks identification results and aerial photographs revealed a discrepancy between the actual area and the area derived from OBIA, Vegetation Indices, and DEMNAS results. According to the volcanic hummocks identification results, 408 volcanic hummocks were successfully detected using the OBIA method. The largest area was found at coordinates (8°17'15.76"S, 113°36'28.3"E) and the smallest was located at coordinates (8°15'29.41"S, 113°22'17.89"E). In addition, petrographic observations and XRD analysis were performed on volcanic hummocks rock samples. The tests showed that volcanic hummocks were predominately composed of andesite, latite basalt, and basalt rocks. Grain size distribution test was also carried out on loose soil samples collected in the volcanic hummocks area. The test were used to determining the direction of the ancient landslide of Mt. Raung. The results indicated that the grain size of vulcanic hummocks near the source of the landslide (in the northern area of the distal zone) was larger, while that of the sand hummocks far from the source of the landslide (in the western area of the distal zone) was smaller.